STOCK MARKET REACTION TO THE COVID-19: EVENT STUDY METHODOLOGY OF PUBLICLY TRADED HEALTHCARE COMPANIES IN INDONESIA - Levina Ameline Moelyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The COVID-19 pandemic caused a stir in the stock market worldwide. Although the healthcare industry was regarded as the better-performing sector during the Pandemic, understanding market behaviour surrounding significant events related to COVID-19 and analysing possible confounding factors to this behaviour will help investors determine stances in future similar circumstances. This study employs event study methodology to find the correlation between variables. Events chosen are the announcement of the first COVID-19 case in Indonesia on March 2nd 2020, the announcement of large-scale distancing measures in the Greater Jakarta area on April 7th 2020, the announcement of health protocol easing on May 17th 2022 and the end of the emergency phase for COVID-19 announcement by WHO, on May 5th 2023 This study aims to picture the 16 healthcare stock market reactions to these events. This study shows that the healthcare stock is not affected by the first, second, third, and fourth event except for MERK on first, second, and third event, and PRIM on first and second event. Older listings age, bigger firm sizes, and pharmaceuticals subindustry showed more resilience during the event study, however no significance obtained.